Estereotipos distópicos en el cine latinoamericano a través de El Club (Pablo Larraín, Chile, 2015) y Zama (Lucrecia Martel, Argentina, 2017) - María Dolores de los Ángeles Pérez Murillo (Les Cahiers ALHIM)
The New Latin American Cinema from the mid-20th century to the present is very rich in dystopian titles, content, places and characters. In this article we have selected two works and two authors with extensive awards and totally new and groundbreaking, since they turn the peripheral places of the Latin American continent and excluded characters into paradigms of a singular film narrative that bets on dystopia.